An analysis of the research team-service user relationship from the service user perspective: a consideration of ‘The three Rs’ (roles, relations, and responsibilities) for healthcare research organisations - Jordan, Melanie; Rowley, Emma; Morriss, Richard K.; Manning, Nick (Wiley, 2015)
Background